Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Becker, A. (International Journal of Sports Science & Coaching, 2018)
Many noteworthy publications offer insights into the qualities that differentiate more and less successful athletes and also provide tested mental training regimens and intervention strategics that appear to have a positive impact on performance. A consultant may take several months or even years to help an athlete develop and implement techniques such as self-talk strategies, mental imagery scripts and pre-performance routines; however it might only take one negative reaction or demeaning phrase from a respected coach to undermine the entirety of the work and leave the athlete in a state of continued struggle. Thus the role of the coach in athlete performance cannot be overstated. As a result many consultants have made efforts to focus their attention on training and helping coaches. One consultant who has done a significant body of work with coaches at all levels is Dr. Andy Gillham, owner of Ludus Consulting.